Study on the migration and structure evolution of the carbon in the slag layer and its effect on the coal slag transformation. (15th March 2022) - Bao, Xiaodan; Gong, Ming; Shen, Zhongjie; Xu, Jianliang; Liang, Qinfeng; Liu, Haifeng
Highlights: Migration and structure evolution of residual carbon in molten slag was studied. Carbon capacity of molten slag increased with temperature and residence time. Carbon structure transferred from graphitic to disordered lattice during migration. Migration and structure evolution of residual carbon promoted slag crystallization. Abstract: The carbon remained/covered in the molten slag layer changes the chemical and physical properties in the entrained flow gasifier and further affects the slag rheology. Our current study focused on the migration and structure evolution of the carbon in the coal slag layer. Besides, the effect of the carbon on the slag transformation was studied as well. The experimental results showed that part of the carbon migrated upward to the molten slag surface during the heating and isothermal process due to its lower density, while the rest reacted with the molten slag or remained as the residual carbon. During the migration process, the iron oxide was reduced to metallic iron enclosure by the carbon via the carbothermal reaction. Both the mass ratio of the carbon that consumed by the slag to initial carbon layer and the carbon capacity of the molten slag increased with the increases of the temperature and residence time. In addition, Raman spectroscopy was used to characterize the structure evolution of the residual carbon. The results showed that with the increase of the slag temperature and residence time, the disordered degree of the residual carbon structure increased and the intensity of the ideal graphite lattice decreased, which promoted the occurrence of the carbothermal reaction. Finally, comparing the carbon migration layer to the non-carbon layer, it was found that the migration, carbothermal reaction, and structure evolution of the carbon promoted the mineral transformation and crystallization behavior of the slag layer.